2015
DOI: 10.1021/bi501127a
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Allosteric Inhibition in Thermus thermophilus Phosphofructokinase

Abstract: The coupling between the binding of the substrate Fru-6-P and the inhibitor phospho(enol)pyruvate (PEP) in phosphofructokinase (PFK) from the extreme thermophile Thermus thermophilus is much weaker than that seen in a PFK from Bacillus stearothermophilus. From the crystal structures of Bacillus stearothermophilus PFK (BsPFK) the residues at positions 59, 158, and 215 in BsPFK are located on the path leading from the allosteric site to the nearest active site and are part of the intricate hydrogen-bonding netwo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 21 publications
(80 reference statements)
0
7
0
Order By: Relevance
“…Temperature plays a crucial role in allosteric mechanisms 29 32 , especially in thermophilic enzymes that remain active at elevated temperatures. The elevation of temperature has been linked in some K-type enzymes 30 to an inversion of allosteric modulation and in others to an enhancement of modulation 32 , 33 . In all these cases, the temperature-induced effects are a consequence of an adjustment in substrate affinity upon allosteric ligand binding.…”
Section: Introductionmentioning
confidence: 99%
“…Temperature plays a crucial role in allosteric mechanisms 29 32 , especially in thermophilic enzymes that remain active at elevated temperatures. The elevation of temperature has been linked in some K-type enzymes 30 to an inversion of allosteric modulation and in others to an enhancement of modulation 32 , 33 . In all these cases, the temperature-induced effects are a consequence of an adjustment in substrate affinity upon allosteric ligand binding.…”
Section: Introductionmentioning
confidence: 99%
“…In this view, it has been shown that allosteric potential can be decreased by using mutagenesis to disrupt specific interactions between fructose-1,6-bisphosphatase and its effector, adenosine monophosphate (33). Recent studies have also shown that engineering can increase allosteric potential, enhancing inhibition of phosphofructokinase by phosphoenolpyruvate (34). An allosteric potential can even be engineered into enzymes where previously one did not exist (35).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies on allostery have focused on the importance of discrete networks of residues that are involved in signal propagation upon effector binding. ,, Such networks have also been identified in the St TrpS complex, where remote mutations can shift the ensemble to favor open conformational states by disrupting hydrogen bonds or salt bridges that form upon COMM domain closure, thereby impeding catalysis. Mutations at the subunit interface can be similarly disruptive .…”
Section: Discussionmentioning
confidence: 99%